2018
DOI: 10.1021/acs.joc.7b03084
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Stereoselective Synthesis of Fluorinated 3,3′-Linked Bisoxindoles

Abstract: A highly diastereoselective organocatalytic method that produces 3-fluoro-3'-hydroxy-3,3'-bisoxindoles and the corresponding 3-fluoro-3'-amino derivatives having two adjacent chirality centers from fluorooxindoles and isatins in high yields is described. The reaction occurs in protic solvents at room temperature, it can be upscaled without compromising yield and stereoselectivity, and chromatographic product purification is not required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Having established a profound interest in organofluorine chemistry, 32 33 34 35 36 37 38 39 40 including C–F bond activation methodology and synthetic or chiroptical sensing applications thereof, 19,21 , 41–43 we decided to investigate the possibility of practical alkyl fluoride to iodide conversion, which would also enable subsequent nucleophilic displacements or other reactions. Hilmersson and co-workers showed that this is possible with YbI 3 (THF) 3 , which has to be prepared from expensive ytterbium(II) iodide (Scheme 1 ).…”
Section: Table 1 Optimization Of the Csp ...mentioning
confidence: 99%
“…Having established a profound interest in organofluorine chemistry, 32 33 34 35 36 37 38 39 40 including C–F bond activation methodology and synthetic or chiroptical sensing applications thereof, 19,21 , 41–43 we decided to investigate the possibility of practical alkyl fluoride to iodide conversion, which would also enable subsequent nucleophilic displacements or other reactions. Hilmersson and co-workers showed that this is possible with YbI 3 (THF) 3 , which has to be prepared from expensive ytterbium(II) iodide (Scheme 1 ).…”
Section: Table 1 Optimization Of the Csp ...mentioning
confidence: 99%
“…Based on our longstanding interest in fluorinated compounds, 7,9–20 we decided to screen a variety of chiral stationary phases (CSPs) to separate the enantiomers of the 2‐aryl‐2‐fluoroacetonitriles 1 – 10 by liquid chromatography, Figure 1. It was expected that the development of high performance liquid chromatography (HPLC) conditions that allow baseline separation of 1 – 10 would not be a simple task and most likely be achieved with some of the most frequently used CSPs originally introduced by Pirkle and Okamoto who without a doubt have been the most influential inventors of broadly useful chiral HPLC columns 21–27 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, intense research efforts have been devoted to the construction of enantioenriched oxindoles that have a tertiary fluorinated stereogenic center at the 3-position . Two main strategies, the direct fluorination of 3-alkyl- and 3-aryloxindoles, and the use of 3-fluorooxindoles as the building blocks, , have emerged for their asymmetric syntheses. Recently, the asymmetric Mannich reaction of 3-fluorooxindoles has attracted great interest, and several papers have documented the use of such reactions on the syntheses of 3-fully substituted 3-fluorooxindoles, containing a chiral β-amine fragment (Scheme ).…”
Section: Introductionmentioning
confidence: 99%